2019
DOI: 10.1037/ser0000274
|View full text |Cite
|
Sign up to set email alerts
|

Asian American and Pacific Islander substance use treatment completion.

Abstract: Mental health professionals and administrators work to improve substance use treatment for racially and ethnically diverse populations. However, a national comparison study of Asian Americans and Pacific Islanders (AAPIs) and non-AAPIs substance use outpatient treatment completion has received little attention. The present study examined treatment completion by comparing AAPI clients to White and Latinx clients, and identified demographic and treatment-related moderating factors associated with treatment compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Our search yielded two articles reporting on SUD treatment outcomes data for the intersection of gender and AAPI identity 37,38 . In an analysis of data from SAMHSA's Treatment Episode Data Sets‐Discharge (TEDS‐D) from 2006 to 2011, Garrison and colleagues 37 examined predictors of outpatient substance use treatment completion by racial/ethnic group. Results showed that compared to participants identifying as White, Latinx, and “other” racial/ethnic groups, AAPIs were significantly more likely to complete substance use treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search yielded two articles reporting on SUD treatment outcomes data for the intersection of gender and AAPI identity 37,38 . In an analysis of data from SAMHSA's Treatment Episode Data Sets‐Discharge (TEDS‐D) from 2006 to 2011, Garrison and colleagues 37 examined predictors of outpatient substance use treatment completion by racial/ethnic group. Results showed that compared to participants identifying as White, Latinx, and “other” racial/ethnic groups, AAPIs were significantly more likely to complete substance use treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that compared to participants identifying as White, Latinx, and “other” racial/ethnic groups, AAPIs were significantly more likely to complete substance use treatment. In regard to gender, AAPI women were more likely to complete treatment when compared to White and Latinx women, whereas male completion percentages were similar regardless of racial/ethnic identity 37 . This study restricted analyses to patients receiving outpatient care and excluded individuals receiving medication treatment for OUD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Asians who experienced anxiety/depression increasing to mild levels showed more frequent drug use even when located in communities with greater levels of non-profit SUD service spending. Garrison et al’s study may partially explain these findings on Asians [ 33 ]. Asian participants of the Garrison et al’s study were likely to seek treatment only if their self-reported substance use became "severe” [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Garrison et al’s study may partially explain these findings on Asians [ 33 ]. Asian participants of the Garrison et al’s study were likely to seek treatment only if their self-reported substance use became "severe” [ 33 ]. Asians did not seek the SUD service until their mental health and substance use issues reached a severe level.…”
Section: Discussionmentioning
confidence: 99%